KOMUNIKASI MULTIKULTURALISME DALAM PARANOIA BUDAYA - Suardipa I Putu (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Indonesia is known as a plural nation because it has a cultural background (cultural background) heterogeneous. Cultural heterogeneity is often followed by misinterpretation, leading to the emergence of various social conflicts of cultural paranoia. The presence of the conflict then spawned the attitude of mutual hatred between one society and the other. Multicultural communication becomes a smart solution to prevent and solve these conflicts. The concept of multiculturalism in multicultural communications glorifies differences, while also looking at the nature of humanity as something universal and equal. Multiculturalism sees that the reality of diversity can not be denied. Differences are seen as opportunities to manifest the social and societal nature of humanity with dialogue and communication. Multiculturalism is a given from God, but Bhineka Tunggal Ika is a gift from our ancestors that must be preserved and preserved for the common good as a whole nation. Keywords: Multiculturalism Communication, Cultural Paranoia